PENINGKATAN KETERAMPILAN MEMBACA AWAL MELAUI METODE BERMAIN DENGAN MEDIA PUZZLE KATA PADA KELOMPOK B PAUD ISTIQOMAH SELUPU REJANG - Shinta Anggraini Rishantie; Sri Saparahayuningsih; Yulidesni Yulidesni (Jurnal Ilmiah POTENSIA, 2018)
The problem had in this classroom action research is whether early reading skills in children in the PAUD group of Istiqomah Selupu Rejang can be improved through the method of playing using word puzzle media? This research was conducted with the aim to improve early reading skill in children of group B PAUD Istiqomah Selupu Rejang. Data collection techniques used are with the test techniques for children and observation for teachers. The data analysis technique used is with the average test technique. The results obtained are the improvements that occur in children's early reading skills by achieving an average value of 3.6 with the "good" criteria in cycle I and increasing with an average value of 4.5 with the criteria of "good" in cycle II. So it can be concluded that this research experience peningkatam but only increased quantitatively while qualitatively get a fixed result.